Peningkatan Kualitas Pelayanan Publik Melalui Penerapan Teknologi Informasi dan Komunikasi di Kantor Desa Palewai - Muhammad Hidayat Djabbari; Widyawati; Dewi Sulfa Saguni; Sriayu Pracita; Nimrah Rahmayanti Yusuf; Hanif Kurniadi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The application of information and communication technology (ICT) in public services provides significant opportunities for the development and advancement of rural areas. However, rural governments, as the frontliners in providing public services, face challenges due to a lack of human resources with skills and knowledge in ICT. Therefore, there is a need for continuous efforts to enhance the capacity of human resources through sustained community service activities. The objective of this Community Service Program (PKM) is to improve the quality of public services through the implementation of information and communication technology at the Palewai Village Office. The execution of this program is carried out through three stages of activities. The results of this community service effort include recommendations for using a website as a public information platform, harnessing ICT in public services, and allocating budget resources for infrastructure and facilities that support ICT implementation. This article is of great importance as a reference for carrying out community service activities, especially those related to enhancing the quality of public services through the utilization of ICT in rural governance.